MODEL ANTRIAN FIRST COME FIRST SERVED PADA LAYANAN KESEHATAN - Cendikia Azwar Abdullah; Fariz Bhayu Aji; Marsani Asfi (Jurnal Digit, 2017)
Abstract Registration of medication is the beginning of the entire medical recording process or this is the first service received by a patient upon arrival at a hospital, clinic, health center or otherwise. In the process of registration is the patient got a good impression or not good from a ministry of the agency. Therefore, in this registration system officers should be friendly, courteous, polite, orderly and responsible for the patient to feel cared for and served well. This application application is created using PHP and mysql as storage media. Web-based application registration application which is the end result of this project is expected to help Niatha Pratama Clinic in handling the patient and also beneficial for society, especially people of Cirebon city. Keywords: Registration medication, Website, first,come, served